BARRE, VERMONT, CHARTER AND ORDINANCES OF THE CITY, ch. 14, § 18 at 48, 53 (1904 Vermont Watchman Co.) (Passed 1895). - (:unkn) unknown (My University, 1895)
No person, except on his own premises, or by the consent and permission of the owner or occupant of the premises, and except in the performance of some duty required by law, shall discharge any gun, pistol, or other fire arm loaded with ball or shot, or with powder only, or firecrackers, serpent, or other preparation whereof gunpowder or other explosive substance is an ingredient, or which consists wholly of the same, nor shall make any bonfire in or upon any street, lane, common or public place within the city, except by authority of the city council.
Keywords: DISCHARGE